Peran Fintech Dalam Memperluas Akses Keuangan di Daerah Terpencil : Studi Kasus di Pulau Tello - Fanaetu, Yuternalis Juniter; Zalukhu, Sukur Puji Iman; Telaumbanua, Vita Levda; Zai, Seven Dewira; Sabola, Sesilia Agustina (CV. SINAR HOWUHOWU, 2025)
This research aims to analyze the role of financial technology (fintech) in expanding financial access in remote areas, with a focus on a case study on Tello Island, an area located outside urban areas. On Tello Island, limited infrastructure and minimal access to traditional financial institutions often become obstacles for local communities to access adequate financial services. In this context, fintech has the potential to be a solution to bridge this gap. This research explores how fintech innovations, such as digital payments, online loans, and money transfer systems, can overcome geographic and economic barriers, and increase financial inclusion in the region. The method used in this research involves field surveys and interviews with fintech users, service providers and local communities to gain insight into the impacts and challenges of fintech implementation on Tello Island. It is hoped that the research results will provide an overview of the potential of fintech in supporting economic development and community welfare in remote areas, as well as provide recommendations for the development of more effective and sustainable fintech solutions in similar areas.